Legislative Decree No. 1513, law to handle overcrowding and health protection as a fundamental right of persons incarcerated in Peruvian penitentiaries - Irigoín Cubas, José Rosario (2022)
The purpose of this article is to address the subject of overcrowding in prisons as a problem faced by Peruvian penitentiaries, which affect the right to health and other related rights of the inmates as a result of the state of emergency caused by the worldwide COVID-19 pandemic. Furthermore, we address the subject of the right to health, specifically of those persons serving time in prison and the duty of the State to protect them, given the special conditions in which they live. The legislative actions taken by the State to protect said right are examined; specifically analyzing Legislative Decree No. 1513, which establishes exceptional provisions to reduce the population of inmates in the penitentiaries due to the risk of infection with the coronavirus, with the aim of protecting their right to health.